Tersilochinae (Hymenoptera: Ichneumonidae) from New Zealand. Part 1. Generic key and three new genera - Khalaim, Andrey I.; Ward, Darren F. (Zootaxa, 2018)
The Tersilochinae (Ichneumonidae) from New Zealand are revised in part, with three new endemic genera and seventeen new species described: Aotearoazeus gen. nov., A. bullivantus sp. nov., A. coronetus sp. nov., A. probles sp. nov., Barycnellus gen. nov., B. aucklandellus sp. nov., B. conlisus sp. nov., B. cuvierensis sp. nov., B. globosus sp. nov., B. robustus sp. nov., Diaparsis zealandica sp. nov., Gauldiana gen. nov., G. arantia sp. nov., G. aspiringa sp. nov., G. dubia sp. nov., G. kaweka sp. nov., G. minuta sp. nov., G. nigra sp. nov., G. rotoitia sp. nov., and G. triangulata sp. nov. Zealochus postfurcalis is transferred to the genus Gauldiana (comb. nov.). The genus Diaparsis is recorded from New Zealand for the first time. Keys to genera and species of Tersilochinae occurring in New Zealand are provided.